TRANSATLANTIC INTEGRATION AND DEVELOPED COUNTRIES COMPETITIVENESS PROBLEMS - A. A. Sidorov (Vestnik MGIMO-Universiteta)
Factors and possible consequences of transatlantic integration are elaborated in the article. An overview of the history of transatlantic cooperation is provided. The author highlights the paramount goal of Transatlantic Trade and Investment Partnership (TTIP) - strengthening the positions of its parties in the world economy against the backdrop of global competition. Stalemate in Doha round of WTO trade negotiations as well as depressed state of the European economy also contributed to transatlantic integration. Validity of the EU Commission conclusion on TTIP benefits is examined. Results of TTIP econometric modelling are critically assessed. Problems of the EU-US non-tariff liberalization are analyzed. Efficiency of the EU and US labor markets is compared. Low competitiveness of the EU in comparison to the USA and underlying risks for TTIP economic growth and employment are outlined. High unemployment, difficulties of manufacturing (including high-tech industries thereof) recovery, adverse general business situation in the EU are among such risks. Various modes of regulatory cooperation and possibility of their adoption in TTIP are considered. Harmonization, erga omnes mutual recognition of regulations, bilateral mutual recognition of regulations, mutual recognition of conformity testing are distinguished. Possible implications of the modes of regulatory cooperation on TTIP members competitiveness, competition with emerging economies and global standard setting are examined. Conflict of TTIP goals and motivations is revealed. The existence of economic factors of transatlantic integration as well as overestimation of TTIP benefits (primarily for the EU economy) is concluded.